Answer:
The solution to the equation is;
![\begin{gathered} t=-2 \\ r=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jkjg03x8mada4l7ogg2rz0hmokfdz6yb50.png)
Step-by-step explanation:
Given the system of equation:
![\begin{gathered} 6r-3t=6------1 \\ 8t=-6r-16 \\ 8t+6r=-16------2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/mmqf90zoa3yqvwpt290uaqfl3ejrbtxul7.png)
Solving by elimination:
Let us subtract equation 1 from equation 2;
![\begin{gathered} 8t+6r-6r-(-3t)=-16-6 \\ 8t+3t=-22 \\ 11t=-22 \\ t=(-22)/(11) \\ t=-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5wab9xkqauolkab5a9dkaw9692bctbpe91.png)
since t = -2, we can use equation 1 to solve for r;
![\begin{gathered} 6r-3t=6 \\ 6r-3(-2)=6 \\ 6r+6=6 \\ 6r=6-6 \\ 6r=0 \\ r=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/26ppxhaufmtmsto28f0m1oso13zl1cv117.png)
Therefore, the solution to the equation is;
![\begin{gathered} t=-2 \\ r=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jkjg03x8mada4l7ogg2rz0hmokfdz6yb50.png)